Relationship between cognitive abilities and manual coordination and balance in preschool children - Filip Sadri; Ivo Sadri; Željko Krneta; Jovana Trbojević Jocić; Maja Batez (Exercise and Quality of Life)
Background: The purpose of this research was to investigate the relationship between cognitive abilities and manual coordination and balance in preschool children. Methods: The sample consisted of 41 preschool children aged 6.4±0.8 on average, of both sexes (30 boys and 11 girls). On top of their regular preschool activities, the children attended a school of sports for preschool children - multisport activities and exercises, twice a week. The sample of measuring instruments comprised 4 motor tests (One-leg stand test, Mann’s test, Finger to nose, Front raises) and 2 cognitive tests (Raven's Colored Progressive Matrices, Cognitive Assessment System). Data was analyzed by applying Linear and Binary logistic regression analysis. Results: Based on the results of the research, one may conclude that there is a statistically significant relation between cognitive abilities and manual coordination in the tested sample of preschool children. The defined predictor system, which consisted of cognitive tests, showed a significant relationship with the hand coordination test, which was assessed by the Finger to Nose test with the eyes closed. A significant contribution to the established relation was given by the G factor estimated by Raven's colored progressive matrices. Conclusions: Physical activities contribute to the development of motor skills and thus to the development of some cognitive abilities in children, which is of great importance for their further development.